2014
DOI: 10.1080/03602559.2013.843705
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Complexed Grafted Low Density Polyethylene Films and Its Applicability in Nuclear Medicine as Radiation Shielding Against Technetium-99 m

Abstract: Low density polyethylene films were grafted by poly (acrylic acid). The effects of dose, monomer concentration, solvent, inhibitor and thickness of films were investigated. Adsorption capacities of grafted films of Pb 2þ and Cd 2þ reached up to 20 and 13 (mg/g), respectively. The complexed grafted films in protection of workers against technetium-99 m radiation dangers were investigated. The effects of grafting percentage, thickness and adsorption capacity of ions on shielding efficiency were studied. The tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Besides, polymers proved their performance and applicability in nuclear medicine as radiation shielding against Technetium-99m, where complexed grafted low-density polyethylene films revealed that the protection efficiency of complexed grafted films was higher than in grafted and virgin films (Awadallah-F and Antar 2014). Also, most frequently used polymers such as POM-polyoxymethylene, PAN-polyacrylonitrile, NR-natural rubber, PEApolymethyl acrylate, PPM-poly-phenyl-methacrylate, PET-polyethylene terephthalate (Bhosale et al 2017) and polyamide (nylon 6) (PA-6), polyacrylonitrile (PAN), polyvinylidene chloride (PVDC), polyaniline (PANI), polyethylene terephthalate (PET), polyphenylene sulfide (PPS), polypyrrole (PPy), and polytetrafluoroethylene (PTFE) (Kaçal et al 2019) were studied in terms of their gamma radiation attenuation.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Besides, polymers proved their performance and applicability in nuclear medicine as radiation shielding against Technetium-99m, where complexed grafted low-density polyethylene films revealed that the protection efficiency of complexed grafted films was higher than in grafted and virgin films (Awadallah-F and Antar 2014). Also, most frequently used polymers such as POM-polyoxymethylene, PAN-polyacrylonitrile, NR-natural rubber, PEApolymethyl acrylate, PPM-poly-phenyl-methacrylate, PET-polyethylene terephthalate (Bhosale et al 2017) and polyamide (nylon 6) (PA-6), polyacrylonitrile (PAN), polyvinylidene chloride (PVDC), polyaniline (PANI), polyethylene terephthalate (PET), polyphenylene sulfide (PPS), polypyrrole (PPy), and polytetrafluoroethylene (PTFE) (Kaçal et al 2019) were studied in terms of their gamma radiation attenuation.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Lead metal (Pb) has good ductility and corrosion resistance and is widely used in storage batteries, cable sheathing, paints and pigments, machinery manufacturing, radiation protection, and other industries [1][2][3]. Pb 2+ is a neurotoxin and is a nonessential metal in the ecosystem.…”
Section: Introductionmentioning
confidence: 99%